Mechanisms of GLP-1 receptor-independent renoprotective effects of the dipeptidyl peptidase type 4 inhibitor linagliptin in GLP-1 receptor knockout mice with 5/6 nephrectomy - Hasan, Ahmed A.; von Websky, Karoline; Reichetzeder, Christoph; Tsuprykov, Oleg; Gaballa, Mohamed Mahmoud Salem Ahmed; Guo, Jingli; Zeng, Shufei; Delić, Denis; Tammen, Harald; Klein, Thomas; Kleuser, Burkhard; Hocher, Berthold (Kidney international, 2019)
Dipeptidyl peptidase type 4 (DPP-4) inhibitors were reported to have beneficial effects in experimental models of chronic kidney disease. The underlying mechanisms are not completely understood. However, these effects could be mediated via the glucagon-like peptide-1 (GLP-1)/GLP-1 receptor (GLP1R) pathway. Here we investigated the renal effects of the DPP-4 inhibitor linagliptin in Glp1r-/- knock out and wild-type mice with 5/6 nephrectomy (5/6Nx). Mice were allocated to groups: sham+wild type+placebo; 5/6Nx+ wild type+placebo; 5/6Nx+wild type+linagliptin; sham+knock out+placebo; 5/6Nx+knock out+ placebo; 5/6Nx+knock out+linagliptin. 5/6Nx caused the development of renal interstitial fibrosis, significantly increased plasma cystatin C and creatinine levels and suppressed renal gelatinase/collagenase, matrix metalloproteinase-1 and -13 activities; effects counteracted by linagliptin treatment in wildtype and Glp1r-/- mice. Two hundred ninety-eight proteomics signals were differentially regulated in kidneys among the groups, with 150 signals specific to linagliptin treatment as shown by mass spectrometry. Treatment significantly upregulated three peptides derived from collagen alpha-1(I), thymosin β4 and heterogeneous nuclear ribonucleoprotein A1 (HNRNPA1) and significantly downregulated one peptide derived from Y box binding protein-1 (YB-1). The proteomics results were further confirmed using western blot and immunofluorescence microscopy. Also, 5/6Nx led to significant up-regulation of renal transforming growth factor-β1 and pSMAD3 expression in wild type mice and linagliptin significantly counteracted this up-regulation in wild type and Glp1r-/- mice. Thus, the renoprotective effects of linagliptin cannot solely be attributed to the GLP-1/GLP1R pathway, highlighting the importance of other signaling pathways (collagen I homeostasis, HNRNPA1, YB-1, thymosin β4 and TGF-β1) influenced by DPP-4 inhibition.